Relational quality and uncertainty in common pool water management: an exploratory lab experiment - Marcela Brugnach (Nature Portfolio, 2021)
Abstract If there is one certainty for the sustainable management of water resources is that facing uncertainty is an unavoidable matter. A concern that, in addition to the best available scientific knowledge and models, requires deep insights about the socio relational processes that underlie decision-making. Our objective here is to better understand if and how the socio relational environment in which decisions are made shapes decision-making under uncertainty in common pool water resource management. Our goal is twofold: methodological and analytical. It consists in designing experiments for carrying out uncertainty analysis to explore the influence that the relationships established among decision actors have in making decision choices under uncertainty in management processes. To this end, we developed one experimental game protocol, representing a typical water management scenario: irrigation, which we use to test two different conjectures about the combined effects of uncertainty and relationships. In doing so, we play close attention to the quality of relationships developed among players (acting as water managers), and how these relationships are structured and organized. Initial tests confirmed the importance that the relationships established among players have for coping with uncertainty in managing water resources.